Honesty in Theology? - McKenna, Joseph H. (Heythrop journal, 2001)
There is risk of intellectual dishonesty in the act of modernizing traditional doctrines. One reason theologians reform traditional doctrines is that the original formulations have become incredible to them. This is seldom honestly admitted. It is further dishonestly claimed that new formulations have a direct conceptual link to the old as if the new were the old retold. However, many times the connection between the new theology and the old is in name only, with radically new understanding for an old term. Can we honestly say so? Theology should resuscitate questions of intellectual honesty that were present at the Liberal theology's origins in the interest of maximizing honest theological inquiry. Can theology construct an ethics of belief for itself?